2010
DOI: 10.1038/ng.637
|View full text |Cite
|
Sign up to set email alerts
|

KLF1 regulates BCL11A expression and γ- to β-globin gene switching

Abstract: We show that knockdown of KLF1 in human and mouse adult erythroid progenitors markedly reduces BCL11A levels and increases human gamma-globin/beta-globin expression ratios. These results suggest that KLF1 controls globin gene switching by directly activating beta-globin and indirectly repressing gamma-globin gene expression. Controlled knockdown of KLF1 in adult erythroid progenitors may provide a method to activate fetal hemoglobin expression in individuals with beta-thalassemia or sickle cell disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
301
0
8

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 342 publications
(329 citation statements)
references
References 15 publications
12
301
0
8
Order By: Relevance
“…KLF1 (or EKLF) is a critical erythroid regulator required for adult β-globin transcription (11). Recently it was shown that KLF1 occupies the BCL11A promoter and activates its expression (12,13). Consistent with previous analysis, knockdown of BCL11A or KLF1 results in marked increase in γ-globin expression and serves as positive controls for the RNAi screen.…”
Section: Bcl11a-interacting Partner Proteins In Erythroid Cellssupporting
confidence: 60%
“…KLF1 (or EKLF) is a critical erythroid regulator required for adult β-globin transcription (11). Recently it was shown that KLF1 occupies the BCL11A promoter and activates its expression (12,13). Consistent with previous analysis, knockdown of BCL11A or KLF1 results in marked increase in γ-globin expression and serves as positive controls for the RNAi screen.…”
Section: Bcl11a-interacting Partner Proteins In Erythroid Cellssupporting
confidence: 60%
“…L'étude en a été faite sur la souris « Berkeley » SCD (sickle cell disease) dont le phénotype récapitule bien la maladie drépanocytaire : ané-mie, augmentation des réticulocytes, taux d'HbF bas, durée de vie des globules rouges abrégée. L'introduction d'allèles BCL11A-nul chez cette souris (SCD Bcl11a fl/fl EpoR-Cre + ) corrige ces altérations et restaure un phénotype très voisin de celui de souris témoins d'HbF (HPFH) [8], et simultanément dans un travail expérimental chez la souris [9]. L'action de KLF1 s'exercerait indirectement par une régulation d'expression de BCL11A.…”
Section: Nouvelleunclassified
“…The role of KLF1 and BCL11A in the switching of fetal to adult b-like globin gene expression is of particular interest. 13,14 Since mice do not have a fetal b-like globin gene, we used animals carrying a human b-globin locus transgene (line PAC8. 1 7 ) to investigate this.…”
Section: Generation Of Compound Transgenic Animalsmentioning
confidence: 99%
“…11 In contrast, it was recently shown that KLF1 activates BCL11A expression. 13,14 KLF1 has a critical role in erythroid development, and in mice, its expression increases threefold upon the transition from primitive to definitive erythropoiesis. 15 Analysis of Klf1 knockout embryos revealed lethality at E14.5 due to anemia caused by disrupted fetal liver erythropoiesis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation